PENGARUH CURRENT RATIO DAN INVENTORY TURNOVER TERHADAP RETURN ON ASSET PADA PT. ASTRA INTERNASIONAL Tbk PERIODE 2013-2022 - Eka Putri, Afriana; Sairin (Journal of Research and Publication Innovation, 2024)
This study aims to determine the relationship between Current Ratio, Inventory Turnover and Return On Asset in PT. Astra Internasional Tbk for the period 2013 – 2022. This research method uses a quantitative descriptive method. The samples used in this study are the company's financial statements in the form of balance sheets and income statements of PT Astra Internasional Tbk for the period 2013-2022. The analysis method used is multiple linear regression to test the relationship between Current Ratio, Inventory Turnover, and Return On Asset. Based on the results of the study, it was shown that the Current Ratio variable had no effect on Return On Asset. This result is in line with research conducted by Aris Susetyo (2017). Meanwhile, the Inventory Turnover variable partially has a significant effect on Return On Asset. These results are in line with research conducted by Linda & Lauw (2017). The results of the F statistical test show that the variables Current Ratio and Inventory Turnover have a significant effect on Return On Asset.